Collagen and non-collagenous proteins molecular crosstalk in the pathophysiology of osteoporosis. (October 2019) - Licini, Caterina; Vitale-Brovarone, Chiara; Mattioli-Belmonte, Monica
Graphical abstract: Representative drawing of the interaction between an osteoclast (OC; in violet) and osteoblasts (OBs; in red) and ECM. Collagen and NCPs networking. Highlights: Normal or pathological connections between Collagen and NCPs in bone matrix formation and resorption are far from being elucidated. Anomalies in their amount and structure can cause malformations and defects, such as osteoporosis (OP). Collagen and NCPs crosstalk and possible involvement in OP onset and maintenance is focused. These elements can be useful for the design/development of innovative strategies in bone remodelling. Abstract: Collagenous and non-collagenous proteins (NCPs) in the extracellular matrix, as well as the coupling mechanisms between osteoclasts and osteoblasts, work together to ensure normal bone metabolism. Each protein plays one or more critical roles in bone metabolism, sometimes even contradictory, thus affecting the final mechanical, physical and chemical properties of bone tissue. Anomalies in the amount and structure of one or more of these proteins can cause abnormalities in bone formation and resorption, which consequently leads to malformations and defects, such as osteoporosis (OP). The connections between key proteins involved in matrix formation and resorption are far from being elucidated. In this review, we resume knowledge on the crosstalk between collagen type I and selected NCPs (Transforming Growth Factor-β, Insulin-like Growth Factor-1, Decorin, Osteonectin, Osteopontin, Bone Sialoprotein and Osteocalcin) of bone matrix, focusing on their possible involvement and role in OP. The different elements of this network can be pharmacologically targeted or used for the design/development of innovative regenerative strategies to modulate a feedback loop in bone remodelling.